Colorado's Statewide Antimicrobial Stewardship (AMS) Collaborative Final Results. Facilitating Syndrome-Specific Interventions for Skin and Soft-tissue Infection (SSTI) and Urinary Tract Infection (UTI). (4th October 2017) - Wald, Heidi; Hulett, Teri; Knepper, Bryan; Barber, Gerard; Shihadeh, Kati; Meyer, Marc; Hammer, John
Abstract: Background: Colorado Hospital Association (CHA) led a statewide collaborative to engage hospitals in AMS, focused on interventions for UTI and SSTI. The collaborative goals were to reduce the use of fluoroquinolones (FQs) for UTIs, increase the proportion of diagnosed UTIs meeting objective criteria, reduce exposure to antibiotics with broad Gram-negative activity for SSTI, and shorten treatment durations for UTI and SSTI. We evaluated the effect of the collaborative on these measures. Methods: Diagnostic (UTI) and treatment guidance (UTI and SSTI) were developed by a local expert panel. Collaborative methodology was used to engage local hospital AMS teams in guideline implementation. Teams submitted data for 80 cases during the baseline period (2014) and 20 cases per quarter during the intervention period (October 2015–December 2016) for each condition. Primary analyses were changes in trends of the main outcomes by interrupted time series analysis. Secondary analyses were the aggregate changes in the main outcomes between the baseline and intervention periods. Results: Twenty-seven acute care hospitals (bed range 15–567) participated in the collaborative. Data were reported for 1, 530 UTI and 722 SSTI cases from the baseline period and for 2, 514 UTI and 1, 030 SSTI cases from the intervention. Interrupted time series analyses of the main outcomes are shown in Figure. The trend in exposure to FQs for UTIs decreased significantly from baseline to the intervention ( P = 0.03). Changes in the trends for the other outcomes did not reach statistical significance. In the secondary analyses, exposure to FQs declined from 49% at baseline to 40% during the intervention (UTI), and the proportion of diagnosed UTIs meeting objective criteria increased from 51% to 54% ( P = 0.10). Among SSTI cases, exposure to antibiotics with broad Gram-negative activity declined from 61% to 53% ( P = 0.001), and the median duration of therapy declined from 13 to 11 days ( P < 0.0001). Conclusion: A statewide collaborative successfully engaged hospitals to participate in AMS. Intended changes in prescribing practices for the collaborative were observed; however, the degree of success varied by outcome. Additional work is needed to explore factors associated with success or lack thereof among the individual hospitals. Disclosures: H. Wald, Colorado Hospital Association: Consultant, Consulting fee; T. Hulett, Colorado Hospital Association: Consultant and Employee, Salary; G. Barber, Merck: Speaker's Bureau, Speaker honorarium